Legal Aspect of Medical Negligence in India (Indian Internet Journal of Forensic Medicine and Toxicology, 2015)
Nowadays, public awareness about medical negligence in India is growing rapidly, and thus hospital managements are increasingly facing complaints regarding the facilities, standards of professional competence, and the appropriateness of their therapeutic and diagnostic methods. After the Consumer Protection Act (CPA), 1986, has come into force some patients have filed legal cases against doctors, have established that the doctors were negligent in their medical service, and have claimed and received compensation. As a result, a number of legal decisions have been made on what constitutes negligence and what is required to prove it. Against this background, aims of this work are to present a summary of legal decisions related to medical negligence and also focus that what constitutes negligence in civil and criminal law, and what is required to prove it.
Keywords: Medical negligence; Gross negligence; Rashness; Criminal law; Medical profession; Consumer protection act; Doctor– patient relationship